Sexual dimorphism and distribution OF Daphne laureola L. in the Bohor area - Jagrič, Miha (Acta silvae et ligni, 2013)
Gynodioecious Daphne laureola L. is one of six species of the genus Daphne L. native to Slovenia. The main goals of this research were to determine the distribution of Daphne laureola in the Bohor area, the sexual structure of populations and its correlation with site conditions, and whether morphological differences exist between females and hermaphrodites beyond those of flower structure. Four research plots located on the north side of Bohor were selected - two in each altitude range. A total of 277 plants were studied to determine the sexual structure of the populations, 90 of which were additionally studied for sexual dimorphism. The species was recorded for the first time in quadrant 9959/1 of the Central European flora mapping grid, extending its previously known distribution. The share of female plants was between 3.17% and 47.17% and was lower at higher altitudes. The frequency of plants, morphological traits, and the proportion of female individuals are highly correlated with environmental factors. Plants bore more flowers at higher altitudes, and leaves were longer, with rounder tips and sharper bases.The majority of morphological differences between females and hermaphrodites were minor and not statistically significant.
Keywords: Daphne laureola L.; lovorolistni volčin; spolni dimorfizem; razširjenost vrste; Bohor; Bohor reedbuck; spolna struktura; morfometrijska analiza